(untitled) (International Journal of Engineering and Computer Science, 2017)
major use of the bar-coding is to secure the data using barcodes. The concept of 2-D barcodes is of great relevance for use in wireless data transmission between handheld electronic devices. In a general setup of barcode standalone systems, any file on a cell phone, for example, can be transferred to a second cell phone through a series of images on the LCD which are then captured and decoded through the barcode scanner of the second cell phone. In the proposed system, a new approach for data modulation in high capacity 2-D barcodes is introduced, where in the High capacity 2 D barcode of 448*63 pixels is used to barcode the data and thereby transmitted through any wireless or wired medium. The proposed barcode has a high capacity of encoding the large amount of data by making use of MD5 secure hashing algorithm for uniquely identifying the data. The data is hashed using MD5 algorithm and thereby retrieved by cross hashing the values decoded from the barcode. The proposed bar-coding and barcode modulation technique makes use of the latest technology for generating and reading the barcodes and thereby avail users to securely transmit the data. In this paper we have propose the survey of barcode types and compare this with high capacity 2D barcode.